Sharing the archive: Using web technologies for accessing, storing and re-using historical data. Issue 2 (July 2018) - Finnane, Mark; Kaladelfos, Andy; Piper, Alana
Historical data pose a variety of problems to those who seek statistically based understandings of the past. Quantitative historical analysis has been limited by researcher's reliance on rigid statistics collected by individuals or agencies, or else by researcher access to small samples of raw data. Even digital technologies by themselves have not been enough to overcome the challenges of working with manuscript sources and aligning dis-aggregated data. However, by coupling the facilities enabled by the web with the enthusiasm of the public for explorations of the past, history has started to make the same strides towards big data evident in other fields. While the use of citizens to crowdsource research data was first pioneered within the sciences, a number of projects have similarly begun to draw on the help of citizen historians. This article explores the particular example of the Prosecution Project, which since 2014 has been using crowdsourced volunteers on a research collaboration to build a large-scale relational database of criminal prosecutions throughout Australia from the early 1800s to 1960s. The article outlines the opportunities and challenges faced by projects seeking to use web technologies to access, store and re-use historical data in an environment that increasingly enables creative collaborations between researchers and other users of social and historical data.